2020
DOI: 10.1016/j.omtn.2019.11.022
|View full text |Cite
|
Sign up to set email alerts
|

Epigenetic Regulation of m6A Modifications in Human Cancer

Abstract: N6-methyladenosine (m6A) is the most prevalent internal RNA modification, especially within eukaryotic messenger RNAs (mRNAs). m6A modifications of RNA regulate splicing, translocation, stability, and translation into proteins. m6A modifications are catalyzed by RNA methyltransferases, such as METTL3, METTL14, and WTAP (writers); the modifications are removed by the demethylases fat mass and obesity-associated protein (FTO) and ALKBH5 (ALKB homolog 5) (erasers); and the modifications are recognized by m6A-bind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
138
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 187 publications
(140 citation statements)
references
References 74 publications
2
138
0
Order By: Relevance
“…Other methods include MAZTER-seq, RNAmod, FunDMDeep-m 6 A and m 6 A-REF-seq ( 72 - 76 ). Table I summarizes the methods of m 6 A methylation detection ( 7 ). These findings have provided insight into the mammalian genome-wide mapping of m 6 A modifications and unveiled the importance of dynamic mRNA modifications on gene expression.…”
Section: M 6 a Methylationmentioning
confidence: 99%
See 1 more Smart Citation
“…Other methods include MAZTER-seq, RNAmod, FunDMDeep-m 6 A and m 6 A-REF-seq ( 72 - 76 ). Table I summarizes the methods of m 6 A methylation detection ( 7 ). These findings have provided insight into the mammalian genome-wide mapping of m 6 A modifications and unveiled the importance of dynamic mRNA modifications on gene expression.…”
Section: M 6 a Methylationmentioning
confidence: 99%
“…Recent studies have found that, in addition to mRNA, m 6 A also occurs in rRNA, tRNA, small nucleolar RNAs, microRNAs (miRNAs or miRs) and long non-coding RNAs ( 5 , 6 ). The rapid development of next-generation sequencing technology and epigenetic research have assisted in the precise assessment of the in vivo methylation state of m 6 A sites at single-nucleotide resolution ( 7 ). Approximately 1/4 of transcripts harbor m 6 A modifications, which are mainly enriched around the stop codons, within long internal exons in the 5′ and 3′ untranslated regions (UTRs) at the consensus motif RRACH (R=A or G, H=A, C or U) ( 8 ).…”
Section: Introductionmentioning
confidence: 99%
“…N6-methyladenosine (m6A) modification is one of the most frequent chemical modifications in eukaryotic mRNAs. 4 Emerging evidence suggests that aberrant m6A RNA methylation plays a critical role in cancer through various mechanisms, 5,6 such as mRNA stability, splicing, and translation. 7 The level of m6A methylation is regulated by methyltransferases, demethylases, and binding proteins.…”
Section: Introductionmentioning
confidence: 99%
“…m6A is the most prevalent internal RNA modification. Abnormal changes in m6A levels of regulators are closely related to the development of tumors [21]. Increasing evidence indicates that m6A can regulate gene expression, which in turn regulates the cellular processes of cell self-renewal, differentiation, invasion, and apoptosis [10,22].…”
Section: Discussionmentioning
confidence: 99%